International ethics - Frost, Mervyn; Sage eBooks (Los Angeles, [Calif.] : SAGE, 2011)
The four volumes of this collection examine the highly relevant issues of international ethics under three broad headings: the moral standing of states; the moral standing of non-state actors; the ethics of international relations.
Specialized.
Description based on print version record.
Includes bibliographical references.
Keywords: International relations -- Moral and ethical aspects; Political ethics; Electronic books